EVALUASI IMPLEMENTASI KURIKULUM MERDEKA PADA MATA PELAJARAN PENDIDIKAN JASMANI DI SEKOLAH DASAR KECAMATAN GEMBONG KABUPATEN PATI - Adji, Tito Pangesti; Shufa, Naela Khusna Faela (Majalah Ilmiah Olahraga (MAJORA), 2024)
Tujuan penelitian ini adalah untuk mengevaluasi kualitas implementasi kurikulum merdeka pada muatan pendidikan jasmani di sekolah dasar di Kecamatan Gembong Kabupaten Pati. Model evaluasi yang digunakan dalam penelitian ini adalah Model Kontradiksi. Partisipan penelitian ini terdiri dari kepala sekolah, guru pendidikan jasmani dan siswa dari lima sekolah di Kecamatan Gembong. Teknik pengumpulan data meliputi survei, kuesioner, dan wawancara. Penelitian ini melibatkan 10 siswa, 5 kepala sekolah, dan 5 guru pendidikan jasmani. Data dalam penelitian ini dianalisis menggunakan analisis deskriptif kuantitatif dan kualitatif. Validator profesional memvalidasi instrumen penelitian. Temuan penelitian menunjukkan bagaimana implementasi kurikulum mandiri pada kelas pendidikan jasmani di sekolah dasar di kabupaten Gembong dievaluasi berada pada kategori "sangat baik". Hasil  analisis  kepala  sekolah  dengan  mean  79,00,  hasil  penilaian dengan  persentase  20%  pada  kategori  "Sangat baik"  ada  (1 orang  kepala  sekolah), kategori  "baik" dengan persentase 20% ada (1 orang kepala sekolah), kategori "cukup"  dengan  persentase  40%  ada  (2 orang  kepala sekolah)  dan kategori "kurang" dengan  persentase  20%  ada  (1  orang  kepala  sekolah). Selanjutnya temuan hasil analisis  guru  Pendidikan jasmanidengan  mean 81,00,  hasil penilaian dengan persentase 40% pada kategori "Sangat baik" ada (2 orang guru), pada kategori "baik" dengan persentase 40% ada (2 orang guru), dan kategori "cukup"  dengan  persentase  20%  ada  (1  orang  guru). Terakhir temuan hasil analisis siswa dengan mean 82,00, hasil penilaian dengan persentase 40% pada kategori "sangat baik" ada (4 siswa), pada kategori "baik" dengan persentase 40% ada (4 siswa) dan kategori "cukup" dengan persentase 20% ada (2 siswa). EVALUATION OF THE IMPLEMENTATION OF THE INDEPENDENT CURRICULUM IN PHYSICAL EDUCATION SUBJECTS IN ELEMENTARY SCHOOLS IN GEMBONG SUB-DISTRICT, PATI DISTRICT Abstracts:The purpose of this study was to evaluate the quality of the implementation of the independent curriculum in physical education content in primary schools in Gembong Sub-district, Pati Regency. The evaluation model used in this study is the Contradiction Model. The participants of this study consisted of principals, physical education teachers and students from five schools in Gembong Sub-district. Data collection techniques included surveys, questionnaires and interviews. This study involved 10 students, 5 principals, and 5 physical education teachers. The data in this study were analyzed using quantitative and qualitative descriptive analysis. Professional validators validated the research instruments. The research findings showed how the implementation of an independent curriculum in physical education classes at primary schools in Gembong district was evaluated to be in the "very good" category. The results of the analysis of school principals with a mean of 79.00, the results of the assessment with a percentage of 20% in the "Very good" category there are (1 principal), the category "good" with a percentage of 20% there are (1 principal), the category "sufficient" with a percentage of 40% there are (2 principals) and the category "less" with a percentage of 20% there are (1 principal). Furthermore, the findings of the analysis of physical education teachers with a mean of 81.00, the results of the assessment with a percentage of 40% in the "Very good" category there are (2 teachers), in the "good" category with a percentage of 40% there are (2 teachers), and the "sufficient" category with a percentage of 20% there are (1 teacher). Finally, the findings of student analysis results with a mean of 82.00, the results of the assessment with a percentage of 40% in the "very good" category there are (4 students), in the "good" category with a percentage of 40% there are (4 students) and the "sufficient" category with a percentage of 20% there are (2 students).